The Effect Of Liquidity And Capital Structure On Profitability And Its Implications For Firm Value (A Case Study Of Transportation And Logistics Sector Companies Listed On The Indonesia Stock Exchange For The 2022-2024 Period) - Annisa Fitri Anggraeni; Adni Salma Laeli (Dinasti Accounting Review, 2026)
This study aims to examine the effect of liquidity and capital structure on profitability and its implications for firm value in transportation and logistics sector companies for the 2022–2024 period. The research population consists of all transportation and logistics companies listed on the Indonesia Stock Exchange. Using a purposive sampling technique, 31 companies were selected as the sample. The analytical method employed is panel data regression with a Random Effect Model (REM) approach, supplemented by the Sobel test to examine indirect effects through the intervening variable. In this study, liquidity is measured by the Current Ratio (CR), capital structure by the Debt to Equity Ratio (DER), profitability by Return on Assets (ROA), and firm value by Price to Book Value (PBV). The results indicate that, partially, liquidity has no significant effect on firm value, while capital structure has a significant effect on firm value. Furthermore, liquidity and capital structure do not significantly affect profitability, and profitability itself does not significantly influence firm value. Simultaneously, liquidity and capital structure have a significant effect on both firm value and profitability. However, profitability is not yet able to mediate the relationship between liquidity and capital structure on firm value.